2019
DOI: 10.1007/s11846-019-00372-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities triggered by cloud sourcing: a stage-based model of business model innovation

Abstract: Current research offers very limited insights on the process of how the adoption and continued use of cloud sourcing might trigger and push the development of business model innovation and affect the competitive advantage of a firm. Applying an abductive approach, with two longitudinal case studies of cloud sourcing firms, and a theoretical framework based on stage-based models of business model innovation and the dynamic capability view of the firm, we develop a model of stage-based business model innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Dynamic capabilities are linked to many research fields, such as sustainable BMI (Bocken & Geradts, 2019), organizational search (Zhao et al, 2019), international social purpose organizations (De Silva et al, 2019), BMI in mergers and acquisitions of technology‐advanced firms (Čirjevskis, 2019), cloud‐sourcing in stage‐based BMs (Muhic & Bengtsson, 2019), and BMI in family firms (Weimann et al, 2019). Although little direct connection could be made between the articles themselves regarding the research area that is linked to dynamic capabilities, we found some similarities in the contributions, as well as in the future directions for the specific research fields.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic capabilities are linked to many research fields, such as sustainable BMI (Bocken & Geradts, 2019), organizational search (Zhao et al, 2019), international social purpose organizations (De Silva et al, 2019), BMI in mergers and acquisitions of technology‐advanced firms (Čirjevskis, 2019), cloud‐sourcing in stage‐based BMs (Muhic & Bengtsson, 2019), and BMI in family firms (Weimann et al, 2019). Although little direct connection could be made between the articles themselves regarding the research area that is linked to dynamic capabilities, we found some similarities in the contributions, as well as in the future directions for the specific research fields.…”
Section: Resultsmentioning
confidence: 99%
“…Firms can apply digital technologies for improved or new processes internally and with their supply chains and their environment and use them for developing their business models. In this special issue, Devece et al (2019) examine crowdfunding, Muhic and Bengtsson (2019) discuss cloud computing, and Miranda et al (2019) investigate consumers' perceptions regarding the credibility of YouTuber-generated product content (YGPC). With respect to digital technologies, the internal and external sources might build the basis for value creation and value propositions, but the value capture among sources is often endangered by serious tensions among partners (Fredrich et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed before, the innovation focus is mostly limited to food alone. Future researchers should broaden the perspective towards the restaurant structure and processes as well as business model innovation [17,[162][163][164][165]. The still neglected integration of the customers into the innovation process seems to be imperative as they are an important driver to enhance the agility in the front end of innovation [166][167][168][169][170][171].…”
Section: Discussionmentioning
confidence: 99%